[OP.5B.03] POPULATION-BASED REFERENCE VALUES FOR PULSATILE HEMODYNAMICS IN MIDDLE-AGED AND ELDERLY INDIVIDUALS – RESULTS OF THE HEINZ NIXDORF RECALL STUDY. (September 2016) - Weber, T.; Wassertheurer, S.; Hametner, B.; Parragh, S.; Moebus, S.; Pundt, N.; Mahabadi, A.A.; Roggenbuck, U.; Lehmann, N.; Stang, A.; Jöckel, K.H.; Erbel, R.
Abstract : Objective: Pulsatile hemodynamics (central pressures, antegrade and backward waves, aortic stiffness) are independent predictors of major cardiovascular events. Population-based reference values for wave separation analysis (WSA) based parameters (amplitude of forward wave – Pf and backward wave – Pb) in middle-aged and elderly individuals are currently missing. Design and method: In 2690 participants from the population-based Heinz Nixdorf Recall Study, we performed high-fidelity radial tonometry, calibrated waveforms with brachial blood pressures and processed them with a transfer function to derive central pressures. Pulse wave analysis (PWA; SphygmoCor system) yielded measures of incident pressure waves (P1) and wave reflections (Augmentation Index – AIx, Augmentation Pressure - AP). Using recently validated Windkessel-model based flow curves, WSA was performed, yielding Pf and Pb (ARCSolver method). Aortic pulse wave velocity (aoPWV) was estimated with a validated formula, including systolic blood pressure, age, and waveform characteristics. Results: 50.2 % of participants were female, mean age was 69 years (range 55–86), mean brachial blood pressure 129/75 mmHg, 55.8% took antihypertensive drugs. A minority of participants had diabetes (6.0%) or cardiovascular disease (11.4%), they were excluded from the analysis. Main determinants of pulsatile hemodynamics were age and gender. Heart rate and ejection duration was stable across all age groups. Central pulse pressure increased with increasing age in men and women, due to an increase in systolic and a decrease in diastolic pressures. PWA-derived P1 as well as WSA-derived Pf (both measures of the incident pressure wave) were higher in men than in women, with only Pf showing a clear increase with age. PWA-derived measures of wave reflections (AIx, AP) were higher in women than in men, and increased with age more consistently in men. Pb did not differ between sexes, and increased with age in men and in women. AoPWV showed the most prominent increase with age in both sexes. Conclusions: We provide age-specific reference values for central pulsatile hemodynamics in a general population cohort. Distribution of PWA- and WSA- derived measures shows some similarities, but differs in important aspects. Most notable, age-associated changes are more obvious with WSA-derived parameters. Figure. No caption available.